2014
DOI: 10.1139/cjfas-2013-0418
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of marine stock enhancement: a case study based on the highly piscivorous Japanese Spanish mackerel

Abstract: Abstract:We used a before-after control-impact design to quantify the genetic effects of the large piscivorous Japanese Spanish mackerel (Scomberomorus niphonius) stock enhancement program on wild populations in the Seto Inland Sea. Samples of 1424 wild and 230 hatchery fish collected from 13 sites around Japan were genotyped using five microsatellite markers. A total of 758 wild and 103 hatchery fish were sequenced for the mitochondrial DNA D-loop region. The population structure of Japanese Spanish mackerel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Similar to this study, stock enhancement programs for Pacific herring in northern Japan (Kitada et al ), Japanese Spanish mackerel off the western coast of Japan (Nakajima et al ), and red drum in the Gulf of Mexico (Carson et al ) also reported no change in genetic diversity metrics despite measurable contributions of stocked individuals to the local spawning population (Pacific herring) and subadult populations (Japanese Spanish mackerel and red drum) in the wild. These programs incorporated aspects of the “Responsible Approach” (Blankenship and Leber ) by using native broodstock and periodically rotating these individuals out of production to increase hatchery effective population size per generation.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to this study, stock enhancement programs for Pacific herring in northern Japan (Kitada et al ), Japanese Spanish mackerel off the western coast of Japan (Nakajima et al ), and red drum in the Gulf of Mexico (Carson et al ) also reported no change in genetic diversity metrics despite measurable contributions of stocked individuals to the local spawning population (Pacific herring) and subadult populations (Japanese Spanish mackerel and red drum) in the wild. These programs incorporated aspects of the “Responsible Approach” (Blankenship and Leber ) by using native broodstock and periodically rotating these individuals out of production to increase hatchery effective population size per generation.…”
Section: Discussionsupporting
confidence: 82%
“…Utter et al 1987;Wenne 1992;Poteaux and Berrebi 1997;Halvorson et al 2001;Was et al 2004;Poćwierz-Kotus et al 2007;Wenne et al 2007;Filipowicz et al 2008;Beaumont et al 2010;Wenne et al 2011;Kohout et al 2013;Nakajima et al 2014). Microsatellites are regularly used in fisheries related applications and research (Was and Wenne 1998;Griffiths et al 2013;Perrier et al 2013;Pukk et al 2013;Bernaś et al 2014;Koljonen et al 2014;Thaulow et al 2014;Valiquette et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Publicly available mtDNA‐CR sequences (305 bp without gaps and missing data, n = 720) and microsatellite genotypes at five loci ( n = 1331) in wild S. niphonius were used (Nakajima et al ., , b ), excluding the sample collected in South Korea and those of hatchery‐reared fish from the original data. All loci were scored by capillary electrophoresis using an ABI PRISM 3130xl Genetic Analyzer (Applied Biosystems; http://www.apliedbiosystems.com) with fluorescent dye‐labelled primers and there was no evidence for scoring error caused by stuttering, large allele dropout, or null alleles (Nakajima et al ., ). The samples were collected from major distribution areas in Japan during 2001–2010 ( Table and Fig .…”
Section: Methodsmentioning
confidence: 99%
“…The sample included some 2 year old fish, but they were matured. As no significant difference was found in the haplotype and allele frequencies (Nakajima et al ., ) by an exact test for population differentiation (Raymond & Rousset, ), the samples were combined within each sampling period and denoted as SIS_1 and SIS_2,. The other samples were young immature fish collected in Tosa Bay (TSB), Shibushi Bay (SBS), Kasasa (KSA), Ise Bay (ISB), Wakasa Bay (WKB) and Goto Island (GOT).…”
Section: Methodsmentioning
confidence: 99%